Process work in urgency and emergency in interface with the death - Dell´Acqua, Magda Cristina Queiroz [UNESP]; Tome, Luciana Yoshie [UNESP]; Popim, Regina Célia [UNESP] (My University, 2013)
This qualitative study aimed to understand the experience of nursing professionals in the working process with adult patients and their families who experience the death event in emergency rooms. One analyzed narratives of 12 professionals, from an emergency room in a university hospital of high complexity, in Botucatu, São Paulo. Data collection occurred from December 2008 to April 2009, through semi-structured interviews. Using content analysis, the central theme emerged: The organization of work in urgency and emergency rooms, with four subcategories: Death as a working routine, Teamwork, Motivation at Work, and Death at a teaching hospital. One concluded that the possibilities of personal and professional growth, the need, and the desire to intervene were identified as motivators for working in emergency rooms, even when it is permeated by death.

Estudio cualitativo cuyo objetivo fue comprender la experiencia de profesionales de enfermería en el proceso de trabajo con paciente adulto y su familia que experimentan el evento de la muerte en la sala de emergencia. Analizadas narrativas de 12 profesionales de primeros auxilios de hospital universitario de alta complejidad, en Botucatu, São Paulo, Brasil. La recolección de datos ocurrió de diciembre de 2008 a abril de 2009, por medio de entrevistas semiestructuradas. Utilizando el análisis de contenido, el tema central emergió: La organización del trabajo en urgencia y emergencia, con cuatro subcategorías: Muerte como rutina de trabajo; Trabajo en equipo; Motivación en el Trabajo; y Muerte en hospital universitario. Las posibilidades de crecimiento personal y profesional, la necesidad y el deseo de intervenir fueron identificados como factores de motivación para el trabajo en urgencia y emergencia, incluso cuando permeada por la muerte.

Estudo qualitativo que objetivou compreender a experiência dos profissionais de enfermagem no processo de trabalho junto a paciente adulto e sua família que vivenciam o evento morte em sala de emergência. Analisadas narrativas de 12 profissionais, de pronto-socorro em um hospital universitário de alta complexidade, em Botucatu-São Paulo. A coleta de dados ocorreu de dezembro de 2008 a abril de 2009, por entrevistas semiestruturadas. Utilizando análise de conteúdo, emergiu o tema central: A organização do trabalho em urgência e emergência, com quatro subcategorias: Morte como rotina de trabalho; Trabalho em equipe; Motivação no trabalho e Morte no hospital-escola. Concluí-se que as possibilidades de crescimento pessoal e profissional, a necessidade e desejo de intervir foram apontadas como motivadores para o trabalho em urgência e emergência, mesmo quando permeado pela morte.
El proceso de trabajo en urgencia y emergencia en interfaces con la muerte
O processo de trabalho em urgência e emergência em interface com a morte
Keywords: Nursing process; Death; Emergency nursing; Qualitative research; Procesos de enfermería; Muerte; Enfermería de urgencia; Investigación cualitativa; Processos de enfermagem; Morte; Enfermagem em emergência; Pesquisa qualitativa